The Mediating Effect of Dividend Policy on Profitability and Market Value Added on Stock Prices in Retail Companies in Indonesia - Simbolon, Aditya Jono; Sihotang, Ronny Buha; Malau, Harman (International Journal of Business, Law, and Education, 2024)
The purpose of this study was first to examine the simultaneous and partial effects of Profitability (ROE) and Market Value Added (MVA) on stock prices in Retail companies listed on the IDX. Second to examine the mediating effect of dividend policy (DPR) between Profitability (ROE) and Market Value Added (MVA) on stock prices in Retail companies on the Indonesia Stock Exchange. This research approach is quantitative which is associative in nature. The population used for this study were retail companies listed on the IDX in the 2019-2022 period totaling 13 companies. The sample technique uses a census technique where all companies are used as research samples so that 4 consecutive years of observation data are obtained with a total of 52 data observations. The data analysis technique uses Oldineray Least Square multiple linear regression andPath Analysis by conducting partial (t test) and simultaneous (F test) tests. The results of this study prove that in the first model partially profitability (ROE) has a significant effect on dividend policy (DPR), while Market Value Added (MVA) has no significant effect on dividend policy (DPR). The results of simultaneous testing prove that ROE and MVA simultaneously have a significant effect on dividend policy (DPR). The research results in the second model partially profitability (ROE) has no significant effect on stock prices, while Market Value Added (MVA) has a significant effect on stock prices. The results of simultaneous testing prove that ROE and MVA simultaneously have a significant effect on stock prices. The results of the third model in path analysis testing can be proven that dividend policy (DPR) is able to mediate the relationship between profitability (ROE) and stock prices. Dividend policy (DPR) is not able to mediate the relationship of Market Value Added (MVA) to stock prices.